Boards of Directors in Russian Publicly Traded Companies in 1998-2014: Structure, Dynamics and Performance Effects - Alexander Muravyev (Institute of Labor Economics (IZA), 2016)
This paper provides new evidence on the structure, dynamics and performance effects of corporate boards in publicly traded companies in Russia. It takes advantage of a new and unique longitudinal dataset of virtually all Russian companies whose shares were traded in the RTS/MICEX/MOEX over 1998-2014. The analysis highlights a number of strong trends in the evolution of boards of directors, such as the declining participation of insider directors and the increasing participation of foreign and female directors. It also shows that board characteristics are linked to company performance (the market-to-book ratio, Tobin's Q, ROE and ROA), suggesting that boards of directors play a non-trivial role in corporate governance in Russia. Testing for structural breaks in the relationship between board composition and firm performance provides some evidence of the changing role of corporate boards over time.
Keywords: G34; L22; 330; board of directors; publicly traded companies; corporate performance; Russia